Dietary advanced glycation end products (dAGEs): An insight between modern diet and health. (30th July 2023) - Tian, Zhaoqing; Chen, Shasha; Shi, Yiheng; Wang, Panpan; Wu, Yongning; Li, Guoliang
Graphical abstract: Highlights: Researches of Dietary AGEs are of great significance for food thermal processing. Mechanisms of possible physiological toxicity caused by AGEs were reviewed. Bio-transport in vivo, detection, and inhibition of AGEs were summarized. Challenges and opportunities in the areas involved were tentatively proposed. Abstract: Advanced glycation end products (AGEs) are formed by a series of chemical reactions of amino acids, peptides, proteins, and ketones at normal temperature or heated non-enzymatic conditions. A large amount of AGEs derived from Maillard Reaction (MR) during the process of food heat-processing. After oral intake, dietary AGEs are converted into biological AGEs through digestion and absorption, and accumulated in almost all organs. The safety and health risk of dietary AGEs have attracted wide attention. Increasing evidence have shown that uptake of dietary AGEs is closely related to the occurrence of many chronic diseases, such as diabetes, chronic kidney disease, osteoporosis, and Alzheimer's disease. This review summarized the most updated information of production, bio-transport in vivo, detection technologies, and physiological toxicity of dietary AGEs, and also discussed approaches to inhibit dietary AGEs generation. Impressively, the future opportunities and challenges on the detection, toxicity, and inhibition of dietary AGEs are raised.